Words over war : mediation and arbitration to prevent deadly conflict - Greenberg, Melanie C. ((Carnegie Commission on Preventing Deadly Conflict Series))
Contenido: Introducción. Separación de naciones. Integración de naciones. Intermediación en conflictos no civiles. Conclusión.